AUTOMATIC CAT FEEDER AND LOCATION TRACKER - M Razif, Nur Izzatul Nadia; Mohd Ralim, Nadilah (Journal of Computing Technologies and Creative Content, 2020)
Most of us are obsessed with cats at home, but it is important to take good care of those cat. The common issue faced by the owner of the cat is food. Some pet owners have quite a busy daily schedule at the workplace, leaving the cat alone for some activities or training and business matters for the whole day or days. Therefore, automatic cat feeder and location tracker is invented. The stand-alone modules Arduino UNO and Node MCU ESP8266, together with appropriate sensor types such as Ultrasonic Sensor, Servo Motor and GPS module tracking position, are one of a kind. This product is developed that can feed pets while owners are not available at homes. Through the use of mobile application, owner can click button to the system for the bowl to be refilled. Also, the system sends notification to the owner when there’s critical level on food and water on the bowls. Lastly, it can help pet owner be aware by tracking the location of cat. The outcome of the project is a fully functioning prototype that can interact remotely via Mobile Application. This gives the individual less work, more leisure, and fewer worries as well.